LIMS observations of lower stratospheric ozone in the southern polar springtime of 1978 - Remsberg, Ellis; Harvey, V. Lynn; Krueger, Arlin; Gordley, Larry; Gille, John C.; Russell III, James M. (2019)
The Nimbus 7 limb infrared monitor of the stratosphere (LIMS) instrument operated from October 25, 1978, through May 28, 1979. This paper focuses on its Version (V6) data for the lower stratosphere of the southern hemisphere, subpolar region during the last week of October 1978. We provide profiles and maps that show V6 ozone values of only 2 to 3 ppmv within the edge of the polar vortex at 46 hPa near 60° S from late October through mid-November 1978. There are also low values of V6 nitric acid (∼ 3 to 6 ppbv) and nitrogen dioxide (< 1 ppbv) at the same locations, indicating that conditions were suitable for a chemical loss of Antarctic ozone some weeks earlier. These <q>first light</q> LIMS observations provide the earliest, space-based view of conditions within the lower stratospheric ozone layer of the southern polar region in springtime.